Work-related road traffic crashes in Malaysia: a comparison between fatal and temporary injury cases - Bakar, Harun; Baharudin, Mohd Rafee; Rusli, Rusdi; Md Isa, Mohd Hafzi (Universiti Putra Malaysia Press, 2024)
Introduction: Work-related road traffic crashes have significant implications for both employers and employees, leading to devastating consequences such as fatalities, injuries, and property damage. Despite the increasing focus on road safety research, little attention has been given to identifying factors associated with work-related road crashes. This paper explores and compares the characteristics of fatal cases (FOT) with the characteristics of temporary injury cases (HUS) in work-related road traffic crashes. Materials and methods: Seven years of work-related road crash claim compensation data between 2014 and 2020 was obtained from the Social Security Organization (SOCSO). A total of 546 cases were involved, including 56 FOT and 490 HUS cases. Categorical data analysis techniques were employed to examine the distinctions between FOT and HUS cases. Results: The results indicate a lower representation of transportation sectors in FOT cases, with the corresponding odds approximately 84% lower. Conversely, small and middle enterprises exhibit an odds ratio of about 5.1 times higher in FOT compared to HUS cases. Conclusion: The findings from this study can serve as proactive measures for employers in addressing work-related road traffic crashes. This includes enhancing road safety awareness programs specifically focusing on groups engaged in nighttime shifts and those involved in sending and pickup duties. Considering the distinct risk profiles of large enterprises versus small and medium enterprises, future studies are necessary to clarify the effectiveness of the road safety initiatives undertaken by both types of enterprises.